Vruć vetar (Epizoda 08) - Pronalazak . Hot Wind (Episode 08) - The Invention - Đorđević, Aleksandar (RTV Beograd, 1980)
The eighth episode starts off with Šurda and his family settling in Firga’s apartment, but only after six months of legal battles to get the illegal tenant evicted. On the good side, Šurda is well off as his firm has to pay him off for preventing him from working. However, once he receives the money, Šurda immediately hands in his notice. His wife Vesna who in the meanwhile has become a successful professional and grown increasingly demanding, wants to buy their own apartment and car, but Šurda has his own ideas and decides to take a break. While hitchhiking, Šurda is picked up by truck-driver Krstivoje who is alcoholic and unable to drive anymore: the two of them soon form a partnership with Šurda in the role of driver. His business enterprises develop further when by chance he meets the illegal tenant from Firga’s apartment. He happens to have invented a cure for alcohol and Šurda gets enthusiastic about it. He invests in the project, but after initial success, the whole venture falls through and Šurda loses all his money.